Предмет: Алгебра, автор: dgigit

 sqrt[6]{64} * sqrt[3]{64}


 frac{ sqrt[3]{6}* sqrt[3]{12}  }{ sqrt[3]{9} }

Ответы

Автор ответа: NNNLLL54
0
 sqrt[6]{64} cdot  sqrt[3]{64} =sqrt[3]{sqrt{64}}cdot sqrt[3]{64}=sqrt[3]8cdot sqrt[3]{4^3}=sqrt[3]{2^3}cdot 4=2cdot 4=8\\ili\\sqrt[6]{64}cdot sqrt[3]{64}=sqrt[6]{64}cdot sqrt[6]{64^2}=sqrt[6]{64cdot 64^2}=sqrt[6]{64^3}=sqrt{64}=8\\ frac{sqrt[3]{6}cdot sqrt[3]{12}}{sqrt[3]9}= sqrt[3]{frac{6cdot 12}{9} }=sqrt[3]{8}=sqrt[3]{2^3}=2
Похожие вопросы
Предмет: Литература, автор: silneeva